Autonomous weapons systems: UN expert talks facing failure time to consider alternative formats - Elisabeth Hoffberger-Pippan; Vanessa Vohs; Paula Köhler (Stiftung Wissenschaft und Politik (SWP), 2022)
The Group of Governmental Experts (GGE) has been discussing autonomous weapons systems (AWS) in the UN arms control context since 2017. Russia boycotted the latest round of talks in Geneva in March, in connection with its 24 February 2022 invasion of Ukraine. Regulation of AWS is an increasingly remote prospect, and some representatives even admit privately that the talks may have failed. The new German government's commitment to work to outlaw AWS is increasingly looking like a labour of Sisyphus. Given that the GGE requires unanimity, but constructive cooperation with Russia is off the table for the foreseeable, other forums will need to be found for the international debate on AWS control. Germany must prepare for options within NATO, the European Union and the United Nations. It is clear that any meaningful process presupposes coherent coordination with the NATO partners on all levels. In order to achieve that, Germany must first develop a clear national position on AWS.
Keywords: 320